Surgeon-Powered Robotics in Minimally Invasive Surgery: Case Report from Nepal - Shrestha, Sujan; Gautam, Sujan; Shrestha, Sandip; Subedi, Sushil K; KC, Ajay; Pradhan, Sushan (Journal of Institute of Medicine Nepal, 2023)
Minimally-invasive surgery is the standard of care in many surgical diseases. Robotic surgery has mitigated nearly all limitations of laparoscopic surgery but with a big cost tag. Surgeon-powered robotic instruments were developed with the concept of providing similar advantages to the robotic platforms but with affordable costs. We report three cases of hernia, one hiatus hernia, and two inguinal hernias managed using a surgeon-powered robotic platform.